2021
DOI: 10.1088/1755-1315/788/1/012189
|View full text |Cite
|
Sign up to set email alerts
|

Blood profile and nutrients digestibility of native chickens fed functional diets with different energy and protein level

Abstract: This study aimed to determine the blood profile, pH value of the small intestine and nutrient digestibility of native chickens fed functional diets with different energy and protein levels. The study used 192 DOC of native chickens with rearing up to 14 weeks old. The study was designed in a factorial completely randomized design with two factors. The first factor was the energy level (E1 = 2,800 kcal, E2 = 3,000 kcal), and the second factor was the protein level (P1 = 18%; P2 = 19%; P3 = 20%; P4 = 21%), each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The morphological characteristics of the duodenum and jejunum are modified by dietary ME levels. It has been reported that diets with high ME levels increase the height of the villi in the duodenum [ 35 ]. In the present study, the ME level did not modify the morphological characteristics of the duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological characteristics of the duodenum and jejunum are modified by dietary ME levels. It has been reported that diets with high ME levels increase the height of the villi in the duodenum [ 35 ]. In the present study, the ME level did not modify the morphological characteristics of the duodenum.…”
Section: Discussionmentioning
confidence: 99%